Find the number of all ordered pairs of integers ( a , b ) such that 3 a + 7 b is a perfect square.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
suppose that a=0, then any even value of b will make it a perfect square. the same is true vice versa.
Log in to reply
One more than a perfect square*, while the asked one is the perfect square, also a=0 implies 3^a=1
3^0 + 7^2 = 50
3^0 + 7^ 4 = 2402
3^0 + 7^6 = 117650
3^0 + 7^0 = 2
With b = {0, 2, 4, 6}, none of them is a perfect square.
3^1 + 7^0 = 2^2
3^2 + 7^1 = 4^2
a^n + b^n = c^n of two terms on L.H.S. cannot have answer of n > 2 {Fermat's Last Theorem}.
Since a^2 + b^2 = c^2 does not consist of {3, 7, c}, (a, b) of (1, 0) and (2, 1) are only possibilities.
Answer: 2
Wrong. Fermat's Last Theorem has nothing to do with this problem.
Log in to reply
A higher order based on Fermat's Last Theorem does not consist of 3 2 + 7 2 = c 2 gives some hint that it looked very likely that only (1, 0) and (2, 1) as answers is reasonable. This was the meaning. Although the case does not match with it, we can relate to convince ourselves about a logical result!
Log in to reply
That made no sense.
Fermat's Last Theorem works only in cases where all the three concerned quantities are being raised to the same power. So, as 3.14 (i mean Pi) said, it has nothing to do with this problem.
Problem Loading...
Note Loading...
Set Loading...
Notice that this forces a , b ≥ 0 . By looking through m o d 4 , we can find that exactly one of a, b is an even integer. Assume 3 a + 7 b = n 2 . We can divide this into 2 cases:
7 b = n 2 − 9 x = ( n − 3 x ) ( n + 3 x )
Then, n is an average of 2 powers of 7, which makes n = 3 x + 1 , since not both n − 3 x and n + 3 x is divisible by 7, and n + 3 x > n − 3 x . However, lo g 7 ( 2 × 3 x + 1 ) ∈ N leads to x = 1 , and we have ( 2 , 1 ) as the solution.
3 a = n 2 − 4 9 y = ( n − 7 y ) ( n + 7 y )
with the same reasoning as the first case, n = 7 y + 1 . Also, this leads to y = 0 , hence we have ( 1 , 0 ) as the solution.
In total, there are 2 solutions.